Oral manifestion of Langerhans cell histiocytosis mimicking inflammation - K S Divya (Wolters Kluwer Medknow Publications, 2014)
Langerhans cell histiocytosis (LCH) is a rare idiopathic disease characterized by the clonal proliferation of Langerhans cells. LCH affects five children per million population. The peak incidence is from 1 to 4 years of age. LCH involves the head and neck region quite commonly. Oral soft tissue lesions are also common. The differential diagnosis of oral LCH includes leukemia, neutropenia, prepubertal periodontitis, hypophosphatasia, fibrous dysplasia, and Papillon-Lefevre syndrome. The prognosis of LCH depends on early detection and appropriate management. Surgical management alone is used in 50% of cases with an additional 23% of the lesions being treated with both surgery and radiation therapy. A case of LCH in a 6-year-old girl involving the mid root level of developing first permanent molar with a floating developing tooth bud of permanent second molar mimicking an inflammation is reported.